Automatic audio summarization using Natural Language Processing - Chauhan, Udit; Tiwari, Tarun; R. Anita, (International Journal of Psychosocial Rehabilitation, 2020)
Audio summarization through text summarization is a very important application of Natural Language Processing(NLP). Whenever there is a conversation happening it involves various types of discussions. Important information always gets lost between such jumbled conversations. Consequently, it becomes extremely essential to extract those important key points for future reference. In this paper we aim to implement the automation of the process. The relevant information resulting from the conversation is extracted with the aid of Natural Language Processing techniques by employing text summarization approaches such as Extractive text summarization and Abstractive text summarization.